2018
DOI: 10.2478/pielxxiw-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

The health locus of control and health behaviours declared by students of health sciences

Abstract: Introduction. Health locus of control is an essential factor affecting lifestyle which plays a major role in choosing health behaviours by individuals including young ones. Aim. The aim of the study was the determination of selected conditions of health control and health behaviours in students of health sciences. Material and methods. The study encompassed 175 students of health sciences at the Medical University of Lublin. The multidimensional health locus of control scale (MHLC), version B, by Z. Juczyński … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A significant association was reported for MHLC and dietary patterns [23], body mass index (BMI) [24], quality of life in patients with diabetes [25], the effect of organic food label on food consumption [26], compliance with childhood vaccinations [27], self-assessed health [28], cyberbullying and being victimized [29], and even for mortality [30]. The studies performed in Polish populations revealed a significant association between IHLC and health behaviors, including health nutrition, physical activity and using safety belts in cars, in students of health sciences [31], between PHLC and health behaviors in medical workers [32], and between IHLC, PHLC, and health behaviors in adults from other professional groups [32]. Mazur et al reported a significant correlation between HL as measured with Health Literacy for School-Aged Children (HLSAC) and IHLC and PHLC subscale scores in a group of junior high school students.…”
Section: Introductionmentioning
confidence: 99%
“…A significant association was reported for MHLC and dietary patterns [23], body mass index (BMI) [24], quality of life in patients with diabetes [25], the effect of organic food label on food consumption [26], compliance with childhood vaccinations [27], self-assessed health [28], cyberbullying and being victimized [29], and even for mortality [30]. The studies performed in Polish populations revealed a significant association between IHLC and health behaviors, including health nutrition, physical activity and using safety belts in cars, in students of health sciences [31], between PHLC and health behaviors in medical workers [32], and between IHLC, PHLC, and health behaviors in adults from other professional groups [32]. Mazur et al reported a significant correlation between HL as measured with Health Literacy for School-Aged Children (HLSAC) and IHLC and PHLC subscale scores in a group of junior high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there has been no other research in Poland relating to the general population. However, studies on selected groups have shown that the average scores obtained for the Internal Dimension can range from 25.4 (people working in non-medical professions) [ 117 ] through 25.8 (students of health sciences) [ 118 ] to 26.2 (groups of healthcare professionals) [ 117 ] and for the Chance Dimension from 19.6 (people working in non-medical professions) [ 117 ] through 20.0 (students of health sciences) [ 118 ] to 20.2 (groups of healthcare professionals) [ 117 ]. Foreign research also supports the above findings.…”
Section: Discussionmentioning
confidence: 99%